Kawalan pencemaran sungai dalam melindungi ekologi dan habitat manusia: tinjauan perundangan di Malaysia - Muhammad Rizal Razman,; Carolyn Melissa Payus,; Jamaluddin Md. Jahi, (Universiti Kebangsaan Malaysia, 2010)
The introduction of rubber by the colonial in 1889 and the industrial revolution which involved tin mining had initiated river pollution phenomena that caused interference to human habitat and ecology in Malaysia. In recent years, more and more rivers have been seriously polluted due to rapid urbanisation process and development of industry and infrastructure. Consequently, environmental management through legislative measure was introduced in order to control river pollution and safeguard human habitat and ecology in Malaysia. Nevertheless, the performance of the environmental management efforts through the use of legislation is still found wanting as there are still a number of rivers that are badly polluted and threaten human habitat and ecology. Therefore, this article presents an overview of the relevant legislation in Malaysia to control river pollution in order to safeguard human habitat and ecology and their administration by relevant government agencies